Schwannoma of the cervical vagus nerve: a rare case report - Setty L. N., Chandra Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Schwannomas, also called as neurilemomas, are well-encapsulated, slowly growing tumors that arise from schwann cells of peripheral nerves. Clinically, schwannomas present as asymptomatic, slowly enlarging lateral neck masses and so they tend to present late. The nerve of origin is not often made until the time of surgery. Preoperative diagnosis is aided by imaging studies such as magnetic resonance imaging and computed tomography. The treatment of choice of schwannomas of the neck typically involves complete surgical resection. Rapidly growing tumors with evidence of invasion, or complete loss of nerve function should trigger complete surgical excision of the tumor. Here, we report a rare case of cervical vagal schwannoma in a 45 year old female who got admitted with the complaint of a firm, painless mass on the left side of the neck. The management of the case is discussed along with the relevant literature.